2022
DOI: 10.3389/fnut.2022.982626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interaction between alcohol and meat consumption on the hyperlipidaemia risk among elderly individuals: Evidence from Shanghai, China

Abstract: BackgroundDiet and other lifestyle habits may have an increased effect on blood lipids in older people. This study aimed to examine the associations between diet (meat, fish, and egg), alcohol consumption and blood lipids.MethodsSurveillance data on chronic diseases and their risk factors were collected from Shanghai during 2017–2018. A Kish table was used for sampling 438 older adults, of whom 71 consumed alcohol. Logistic regression was used to test the relationships between diet, alcohol consumption and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Hyperlipidemia, also known as dyslipidemia, is usually associated with elevated triglycerides and total cholesterol in plasma, is developing into one of the main diseases that affect people's daily health. Hyperlipidemia can be divided into primary hyperlipidemia and secondary hyperlipidemia according to pathogenesis, it is reported that hyperlipidemia could occur at different ages and genders, the incidence rate of hyperlipidemia was increased with the age, and the highest incidence occurs between 50-69 years old; many factors including gender [5,6], alcohol consumption [7,8],…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia, also known as dyslipidemia, is usually associated with elevated triglycerides and total cholesterol in plasma, is developing into one of the main diseases that affect people's daily health. Hyperlipidemia can be divided into primary hyperlipidemia and secondary hyperlipidemia according to pathogenesis, it is reported that hyperlipidemia could occur at different ages and genders, the incidence rate of hyperlipidemia was increased with the age, and the highest incidence occurs between 50-69 years old; many factors including gender [5,6], alcohol consumption [7,8],…”
Section: Discussionmentioning
confidence: 99%